QUO-VADIS MULTIKULTURALISME DALAM HISTORIS DAN HISTORIOGRAFI SENI RUPA INDONESIA - Kasiyan, Kasiyan (Sekolah Pascasarjana UGM, 2011)
The multicultural paradigm has become a frequent topic of discussion as its key values con-cerningthe spirit of respecting differences. The fact that differences are commonly considered a threat in Modernistphilosophy has led particularity space becoming increasingly negated. In an Indonesian context,multiculturalism has a long historical basis, one tied inexorably with the nationâs nature as an absoluteconstructed from plural complexity. Hence, multiculturalism should be involved in every cultural activity,at any time and in any context, including the Fine Arts. Within this discipline, multiculturalism hasbeen the main concern, considering that the Fine Arts deal with creativity and aesthetic terminologieswhich cannot be separated from the discussion of differences. What then becomes the main concern is thefact that this multicultural aspect has unconsciously become a quo-vadis reality in other cultural mainstreams.